2017
DOI: 10.3389/fnmol.2017.00144
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary Exercise Promotes Glymphatic Clearance of Amyloid Beta and Reduces the Activation of Astrocytes and Microglia in Aged Mice

Abstract: Age is characterized by chronic inflammation, leading to synaptic dysfunction and dementia because the clearance of protein waste is reduced. The clearance of proteins depends partly on the permeation of the blood–brain barrier (BBB) or on the exchange of water and soluble contents between the cerebrospinal fluid (CSF) and the interstitial fluid (ISF). A wealth of evidence indicates that physical exercise improves memory and cognition in neurodegenerative diseases during aging, such as Alzheimer’s disease (AD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
215
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(220 citation statements)
references
References 55 publications
4
215
0
1
Order By: Relevance
“…Since Aβ clearance was contributed by not only microglia but also astrocytes [27], we further confirmed the effect of DTS I on Aβ clearance in mice primary cortical astrocytes, and the results demonstrate that DTS I could enhance Aβ clearance in primary cortical astrocytes in a dose-dependent manner (Fig. 3d).…”
Section: Dts I Promotes Aβ Clearance Involved With Ampk/ Autophagy Pasupporting
confidence: 67%
“…Since Aβ clearance was contributed by not only microglia but also astrocytes [27], we further confirmed the effect of DTS I on Aβ clearance in mice primary cortical astrocytes, and the results demonstrate that DTS I could enhance Aβ clearance in primary cortical astrocytes in a dose-dependent manner (Fig. 3d).…”
Section: Dts I Promotes Aβ Clearance Involved With Ampk/ Autophagy Pasupporting
confidence: 67%
“…Physical exercise as a therapeutic approach has been shown to significantly attenuate microglia activation in aging [57][58][59]. The improvement in cognitive function was associated with changes in modulation of the microglial phenotype from proinflammatory M1 to antiinflammatory M2 in the corpus callosum, after 28 days of exercise in rats with chronic cerebral hypoperfusion [60].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a study demonstrated that voluntary running for 6 weeks was able to significantly increase glymphatic influx and clearance in aged mice(125). The improvement in glymphatic function coincided with decreased Aβ concentrations (both Aβ40 and Aβ42) and higher synaptic integrity in the cortex and hippocampus of exercised mice.…”
Section: Targeting Glymphatics For Treatment and Prevention Of Svdmentioning
confidence: 99%
“…The improvement in glymphatic function coincided with decreased Aβ concentrations (both Aβ40 and Aβ42) and higher synaptic integrity in the cortex and hippocampus of exercised mice. The authors attributed this to a reduction in reactive astro- and microgliosis and normalization in expression of AQP4 and its polarization(125). Of note was that this study found no difference in BBB permeability after quantifying the extravasation of an intravascular dye between the exercise and control groups.…”
Section: Targeting Glymphatics For Treatment and Prevention Of Svdmentioning
confidence: 99%